Comparison of the formation, filtration performance, and structural characteristic of self-forming dynamic membranes under constant transmembrane pressure and constant filtration flux. Issue 6 (December 2022) - Lv, Miao; Feng, Huajun; Ding, Yangcheng; Pan, Shuping; Qiao, Hua
Abstract: The formation and filtration of self-forming dynamic membranes (SFDMs) can be affected by multiple factors, such as the operating conditions and sludge properties in membrane bioreactors. There has been limited research on the effects of the constant transmembrane pressure and constant filtration flux on the stable filtration of dynamic membranes. In the present study, a large-pore stainless steel mesh (70 µm pore size) was used as the support material for dynamic membrane formation to explore the formation, filtration performance, and structural characteristics of two dynamic membranes, P-SFDM (filtration under constant transmembrane pressure) and J-SFDM (filtration under constant flux), with the same initial filtration flux. The results showed that the stable filtration period of J-SFDM went up to 22.5 h, which was significantly longer than that of P-SFDM (5.5 h) with a higher resistance growth speed. The blocking process of the P-SFDM membrane conformed to the complete blocking model, whereas that of the J-SFDM membrane conformed to the standard blocking model in the initial stage and follows the intermediate blocking model in the later stage. Besides, the P-SFDM cake layer had a higher extracellular polymer content and smaller particle size (106 ± 2 mg·g −1 VSS, 546 ± 63 µm) than that of the J-SFDM cake layer (89 ± 3 mg·g −1 VSS, 615 ± 51 µm). During a 39-day continuous long-term operation, the energy consumptions per ton of water for J-SFDM and P-SFDM were 0.14 kw·h·t −1 and 0.19 kw·h·t −1, respectively. The above results show that the J-SFDM has a longer stable filtration period with lower energy consumption per ton of water. Graphical Abstract: ga1 Highlights: Filtration processes of P-SFDM and J-SFDM were systematically compared. J-SFDM had longer filtration durations and slower membrane resistance growth. Filtration blocking model fitting results of P-SFDM and J-SFDM were different. Energy consumption per ton of water in J-SFDM was lower than that in P-SFDM.